THE BANKING SYSTEM OF UZBEKISTAN CURRENT STATE AND DEVELOPMENT PROSPECTS - Axrorovna , Azlarova Aziza (PT ANTIS International Publisher, 2024)
The article discusses modern reforms aimed at the development of the banking sector in Uzbekistan. The key indicators of this sector are evaluated in dynamics, and problem loans from both commercial banks with state participation and private ownership are analyzed. The analysis revealed that frequent changes in tax legislation and currency policy represent a significant obstacle to the further development of the banking system of Uzbekistan. This can lead to fluctuations in the profitability of financial instruments at the initial stages and in the future contribute to the intensification of crisis processes in the economy. The results of the study can be useful for making strategic decisions on the development of countries with economies in transition.